The Impact of Dual Tasking on Sentence Comprehension in Children With Specific Language Impairment. - Leclercq, Anne-Lise; Majerus, Steve; Prigent, Gaïd; Maillarta, Christelle; Oetting, Janna; Gillam, Ron (Journal of Speech, Language & Hearing Research, 2013)
Purpose: In this study, the authors assessed the hypothesis of a limitation in attentional allocation capacity as underlying poor sentence comprehension in children with specific language impairment (SLI). Method: Fifteen children with SLI, 15 age-matched controls, and 15 grammar-matched controls participated in the study. Sixty sentences were presented in isolation, and 60 sentences were presented with a concurrent choice reaction time task in which colored stimuli randomly appeared at the center of the computer screen. Results: Sentence comprehension was affected by the dual-task condition to a greater extent in children with SLI relative to age controls but not relative to grammatical controls. Conclusion: This study does not support limitations in attentional allocation capacity as representing a core deficit in SLI. Rather, the data show that these children show attentional allocation capacity comparable to that of younger children having similar language level, suggesting that SLI is characterized by a slowed development of both attentional and language domains.